Compliance in Carrying Out Triple Elimination Examination Reviewed from Parity and Husband Support in Pregnant Women at Gondanglegi Public Health Center, Malang Regency - Anggrawati Wulandari; Pratiwi Ade Suryani; Retno Palupi Yonni Siwi; Erma Retnaningtyas (Universitas STRADA Indonesia, 2025)
Background: Triple Elimination is a health program about Elimination of HIV/AIDS, Syphilis and Hepatitis B transmission from mother to child. The lack of compliance of pregnant women in carrying out Triple Elimination examinations during pregnancy is very high. Participation in Triple Elimination examination can increase with strong husband support. Purpose: This study aims to determine the relationship between compliance in conducting Triple Elimination examinations in terms of parity and husband support in pregnant women. Methods: The research design used in this study is quantitative correlation with a cross-sectional approach. With the accidental sampling technique, the sample in this study was 81 pregnant women. The instrument in this study used a questionnaire. Data analysis used Spearman Rank. Results: The results of the study from 81 respondents showed that the majority of respondents were primiparous 47 respondents (58.02%), the majority of respondents had good support from their husbands 64 respondents (79.01%), and the majority of respondents were obedient 42 respondents (51.85%). Analysis using Spearman's rho statistical test obtained the results of Sig. (2-tailed) 0.000 and a correlation value of 0.77, which indicates that the correlation is classified as strong. It’s means there is a relationship between compliance with triple elimination examinations reviewed from parity and husband's support in pregnant women. Conclusion: Pregnant women are required to undergo triple elimination examination and it is expected to be carried out in the first trimester to detect HIV/AIDS, syphilis, and hepatitis B early and to determine further medical action. Research can be carried out smoothly without any obstacles or barriers. The results of this study are expected to be a reference for further researchers who wish to conduct similar studies or continue research with a more specific focus, including exploring additional variables that have not been studied, such as socio-economic, attitudes, support and maternal knowledge about triple elimination examinations.